2019
DOI: 10.1186/s12864-019-6131-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequence properties of certain GC rich avian genes, their origins and absence from genome assemblies: case studies

Abstract: Background More and more eukaryotic genomes are sequenced and assembled, most of them presented as a complete model in which missing chromosomal regions are filled by Ns and where a few chromosomes may be lacking. Avian genomes often contain sequences with high GC content, which has been hypothesized to be at the origin of many missing sequences in these genomes. We investigated features of these missing sequences to discover why some may not have been integrated into genomic libraries and/or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…In mammals, leptin is a hormone secreted by adipocytes and acts on the hypothalamus to suppress eating and obesity ( Halaas et al, 1995 ). Recently, the leptin gene has been identified in some bird and these findings suggest that avian leptin may have a different physiological function from that of lipid metabolism in mammals ( Seroussi et al, 2017 , 2019 ; Beauclair et al, 2019 ; Friedman-Einat and Seroussi, 2019 ). The present study showed that NPGM is a new player in regulating fat deposition in avian species, chicken.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, leptin is a hormone secreted by adipocytes and acts on the hypothalamus to suppress eating and obesity ( Halaas et al, 1995 ). Recently, the leptin gene has been identified in some bird and these findings suggest that avian leptin may have a different physiological function from that of lipid metabolism in mammals ( Seroussi et al, 2017 , 2019 ; Beauclair et al, 2019 ; Friedman-Einat and Seroussi, 2019 ). The present study showed that NPGM is a new player in regulating fat deposition in avian species, chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the ERK1 gene may have been lost in the chicken due to its absence in sequenced chicken genome (Lefloch et al 2008) and the absence of ERK1 protein in chicken brain protein extracts (Buscà et al 2015). Furthermore, the chicken genome assemblies are still incomplete due to technical difficulties imposed by the existence of highly stable secondary gene structures (Beauclair et al 2019). Further studies are required to determine the existence of the ERK1 gene in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of leptin in the peripheral circulation has been questioned because it was not detected in the blood of birds (Seroussi et al, 2016). Recently, the leptin gene has been identified in some birds, and avian leptin is expressed in the digestive organs (Friedman-Einat and Seroussi, 2019; Seroussi et al, 2017; Beauclair et al, 2019; Seroussi et al, 2019). These findings suggest that avian leptin may have a different physiological function from that of lipid metabolism in mammals.…”
Section: Discussionmentioning
confidence: 99%